Clinicoepidemiological characteristics of cutaneous tuberculosis in 1458 Indian patients: a retrospective analytical study from a tertiary care center. (17th May 2022) - Singal, Archana; Kaur, Ishmeet; Jakhar, Deepak; Pandhi, Deepika; Grover, Chander; Gandhi, Vijay
Abstract: Background: Tuberculosis (TB) has been one of the most challenging infectious diseases globally. Cutaneous tuberculosis (CTB) accounts for 0.5–2% of extrapulmonary TB and is often missed owing to its varying morphology and paucibacillary nature. Methods: In this retrospective analytical study, we share our 22‐year experience to describe the clinicoepidemiological features and treatment response of CTB in 1458 Indian patients. In each patient, detailed history was followed by clinical examination, hematological and biochemical investigations, Mantoux testing, chest x‐ray, and other specialized investigations to detect coexisting systemic foci. Clinical diagnosis of CTB was confirmed on histopathology/cytology and response to standard antitubercular treatment (ATT). All details were recorded on a predesigned proforma. Results: Of 1458 eligible patients, 803 were children. The mean disease duration was 15.3 months. Lupus vulgaris (40.4%) was the most common clinical variant, followed by scrofuloderma (32.7%) and lichen scrofulosorum (15.2%). Other variants included tuberculosis verrucosa cutis, gumma, tuberculids, and inoculation TB. Multiple clinical variants were observed in 3.6% of patients. A total of 41.4% of patients had coexistent systemic foci; in lymph nodes (50.4%), lungs (35.6%), bone (10.3%), and abdomen (5.8%). TB foci were also observed at uncommon locations like the eye, central nervous system, and genital organs. Treatment response to ATT was favorable in 99.2%. Interpretation: The burden of CTB still persists in developing countries. The diagnosis is often missed due to the wide spectrum of clinical and histological presentations. Awareness among clinicians of varying aspects of CTB is of paramount importance for early diagnosis and management and will significantly prevent morbidity and disease complications.